2013
DOI: 10.1002/j.0022-0337.2013.77.1.tb05449.x
|View full text |Cite
|
Sign up to set email alerts
|

Predoctoral Prosthodontic Clinical Curriculum for Complete Dentures: Survey in Turkish Dental Schools

Abstract: The aim of this study was to evaluate predoctoral complete denture curricula in the dental schools of Turkey in terms of materials, techniques, and approaches. A questionnaire with twenty-two multiple-choice questions was prepared and sent by e-mail to the directors of the prosthodontic departments of the seventeen long-established dental schools in Turkey. All schools responded for a response rate of 100 percent. All schools (100 percent) reported using irreversible hydrocolloid impression material for prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 18 publications
(24 reference statements)
1
22
1
Order By: Relevance
“…Further, all dental schools taught border molding using a stick modeling compound with a custom tray for the impression making. This result agrees with the finding that all Turkish dental schools used impression compounds for border molding [9], and 98% of the US schools taught border molding with custom trays [5]. Using the stick-modeling compound with a custom tray constituted the standard practice of border molding according to curriculum-compliant textbooks.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Further, all dental schools taught border molding using a stick modeling compound with a custom tray for the impression making. This result agrees with the finding that all Turkish dental schools used impression compounds for border molding [9], and 98% of the US schools taught border molding with custom trays [5]. Using the stick-modeling compound with a custom tray constituted the standard practice of border molding according to curriculum-compliant textbooks.…”
Section: Discussionsupporting
confidence: 86%
“…The questionnaire was based on certain existing studies [5][6][7][8][9] and translated into Japanese. It contained nine multiple-choice questions and the respondents were asked to choose the most appropriate choice related to impression making during removable complete denture fabrication corresponding with the undergraduate students' clinical curriculum on the clinical training in the dental hospital.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…For example, surveys in dental schools, postdoctoral programmes, prosthodontists and general dentists have showed variations, such as the use of an impression compound for border moulding associated with polyvinyl siloxane/polysulfide for final impression in the United States or irreversible hydrocolloid as the preferred material for final impression in the United Kingdom . Another survey in Turkish dental schools revealed that irreversible hydrocolloid impression material for preliminary impression, impression compound for border moulding and zinc oxide eugenol for final impression are the most commonly used materials . A study that included 44 dental schools in the United States surveyed the material and procedures adopted in the undergraduate curriculum and also revealed great variation regarding several aspects of denture construction, such as “selective pressure technique” (71%), border moulding with impression compound for final impression (64%), vent holes in custom trays (59%), visible light‐cured composite resin material for fabrication of custom trays (70%), baseplate wax for relief of the custom trays (73%), open‐mouth technique (86%) and polysulfide material for final impression (39%).…”
Section: Discussionmentioning
confidence: 99%
“…This technique was acquainted as an option with adjusted complete denture where tracing procedure was viewed as hard to perform. This has been adjusted in the undergraduate complete denture educational programs over the world [9,10] In the first appointment, primary impression is made with impression compound or alginate. The lab procedure is like the seven visit denture.…”
Section: Five Visit Denture:-mentioning
confidence: 99%